2016
DOI: 10.3892/ijo.2016.3547
|View full text |Cite|
|
Sign up to set email alerts
|

Repression of Smad4 by miR-205 moderates TGF-β-induced epithelial-mesenchymal transition in A549 cell lines

Abstract: The TGF-β/Smad signaling pathway plays important roles in cancer cell proliferation, apoptosis, differentiation, angiogenesis and epithelial-mesenchymal transition (EMT), which is the key event in the early stages of cancer metastasis and enhances the capability of cell migration and invasion. Smad4 acts as the only Co-Smad of TGF/Smad signaling pathway and plays the key role in TGF-β-mediated EMT. Nevertheless, the mRNA regulation mechanisms of Smad4 in human non-small cell lung cancer (NSCLC) remains largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 41 publications
4
43
0
Order By: Relevance
“…Qiao et al informed that miR‐34a repressed EMT in human cholangiocarcinoma by directing SMAD4 through the TGF‐β/Smad signaling pathway. Zeng et al reported the suppression of SMAD4 by miR‐205 regulates TGF‐β‐induced EMT in Squamous cell carcinoma cell lines. In our experiments, we first introduced TGF‐β1 exogenously to induce EMT progression in cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Qiao et al informed that miR‐34a repressed EMT in human cholangiocarcinoma by directing SMAD4 through the TGF‐β/Smad signaling pathway. Zeng et al reported the suppression of SMAD4 by miR‐205 regulates TGF‐β‐induced EMT in Squamous cell carcinoma cell lines. In our experiments, we first introduced TGF‐β1 exogenously to induce EMT progression in cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is well‐known that miRNAs are involved in the progression of EMT in cancer by directly regulating the expression of their specific target at the posttranscriptional level. It has been indicated that miRNAs play an irreplaceable part in TGF‐β‐induced EMT . Mengtao Ma et al found that MAGI2 promotes TGF‐β1‐induced EMT and migration and invasion of breast cancer cells under the direct action of miR‐487a .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Moreover, SMAD4 has been found to play a key role in EMT. [24][25][26] In order to determine the detailed mechanism of USP17 on EMT, we performed co-immunoprecipitation (co-IP) analysis to detect the interaction between USP17 and SMAD4. The results indicated that USP17 interacted with SMAD4, but there is no interaction between USP17 and SMAD3 ( Figure 5(a)).…”
Section: Usp17 Interacts With Smad4 and Stabilizes Smad4 Through Its mentioning
confidence: 99%
“…Activated TGF‐β receptor regulates transcription of nuclear material through Smad2, 3, and 4 . In the tissues of human kidney and animal models with diabetic nephropathy, hypertensive nephropathy, or PKD, both Smad2 and Smad3 expression were increased.…”
Section: Introductionmentioning
confidence: 99%